ANALYSIS OF THE DYNAMICS, STRUCTURE, AND TRANSFORMATION OF ECONOMIC GROWTH IN SOUTH SULAWESI PROVINCE: TRENDS AND SUSTAINABILITY CHALLENGES - Nur Indah; A. Niniek. F. Lantara (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2026)
South Sulawesi Province serves as a major economic growth center in Eastern Indonesia, characterized by rapid development dynamics over the past decade. This study aims to analyze economic growth patterns, economic structural transformation, sectoral contributions, and identify strategic challenges faced in efforts to achieve sustainable economic development. The research method used is a descriptive quantitative approach with comparative analysis and sectoral decomposition, using secondary time series data for the 2020–2024 period sourced from the Central Statistics Agency. The results show that the South Sulawesi economy has high resilience to external shocks, as evidenced by its rapid recovery after the COVID-19 pandemic and the achievement of an average growth rate of 5.12% per year. Structurally, the economy is still dominated by the primary sector (Agriculture, Forestry, and Fisheries) with an average contribution of 24.08%, followed by the tertiary sector (Trade and Services) and the secondary sector (Construction and Industry). Although there has been a gradual shift towards the service sector, the economic transformation towards industrialization has not been significant. Policy implications emphasize the need to strengthen the downstreaming of primary products, accelerate economic diversification, and equalize infrastructure across regions to create a more robust, balanced, and highly competitive economic structure.